Dual institution experience of extranodal marginal zone lymphoma reveals excellent long‐term outcomes. (8th March 2016) - Starr, Adam G.; Caimi, Paolo F.; Fu, PingFu; Massoud, Mira R.; Meyerson, Howard; Hsi, Eric D.; Mansur, David B.; Cherian, Sheen; Singh, Arun D.; Cooper, Brenda W.; De Lima, Marcos J.G.; Lazarus, Hillard M.; et al.
Summary: Extranodal marginal zone lymphoma (EMZL) is a B‐cell lymphoma arising from mucosa‐associated lymphoid tissue (MALT). The disease characteristics, clinical course and treatment vary considerably based on site of involvement. Because long‐term outcome data for EMZL are limited, we sought to describe the clinical details of a large number of patients with EMZL evaluated at the Case Comprehensive Cancer Center over a 12‐year period to identify prognostic markers including the impact of site of involvement. We identified 211 cases of EMZL involving the stomach (30%), ocular adnexa (19%), lungs (16%) and intestines (9%). Initial treatment included antibiotics (18%), radiation (21%), rituximab (20%), chemotherapy (3%), rituximab + chemotherapy (7%), surgery (17%) or observation (8%). After a median follow‐up of 44·3 months (range 2·2–214·9), median progression‐free survival (PFS) was 68·2 months (95% confidence interval [CI] 54·5–111·3) and median overall survival (OS) has not been reached. Age >60 years, elevated lactate dehydrogenase level (LDH), ≥4 lymph node groups involvement, and high follicular lymphoma international prognostic index (FLIPI) were associated with inferior PFS/OS. In summary, patients with EMZL have excellent prognosis with median OS in excess of 10 years. Age, elevated LDH, advanced disease, and high FLIPI score are associated with worse outcomes.